Thixotropic Supramolecular Gel Based on l-Lysine Derivatives - Suzuki, Masahiro (Gels, 2015)
The dimer l-lysine derivatives, in which two N(α),N(ε)-diacyl-l-lysines were crosslinked by calcium ion, were synthesized through a simply synthetic procedure and their gelation properties were examined. These compounds functioned as an organogelator; especially, the gelators possessing both a linear and a branched alkyl chains had the better organogelation ability and formed the thermally stable and rigid organogel. In addition, some organogels had a thixotropic property, which were responsive to a mechanical stimulus and reversibly underwent the gel–sol transition at room temperature. The thixotropic behavior was confirmed by visual contact and rheological experiments. Furthermore, it was assumed the mechanism of the thixotropic behavior.